Corporate Governance Reform and Real Earnings Management in Nigeria: An Analysis of pre and post mandatory Code of 2018 - Armaya’u Alhaji Sani (Eurasian Journal of Management & Social Sciences)
The paper addressed the question of whether corporate board attributes constrain the effect of REM before and after the mandatory code of 2018 in Nigeria. The data was analysed using panel corrected standard Error (PCSE). The analysis was divided in to pre -period (2016-2017) and post mandatory period (2019-2020). The study established that EM has drastically reduced during the post mandatory period due to strong monitoring by the board. Specifically, I found that independent directors and financial expertise directors significantly reduced the magnitude of real earnings management. Contrary to the research hypothesis, the research established that existence of foreign board member does not constrain the trend of earnings management even after the mandating. Finally, the result also recorded that director’s ownership helps in the implementation of mandatory measures which mitigate the likelihood of REM, both before and after the mandatory period.